(untitled) (Perner’s Contacts, 2021)
A bridge crane is a type of crane that is designed for lifting / lowering and transferring material in the horizontal direction and is used mainly in production halls, warehouses and transship points. A part of the lifting mechanism of the bridge crane is a crane hook on which the load is suspended. Sufficient strength is required from the crane hook in order to be able to withstand high loads relatively well. The most stressed part of the crane hook is the curved inner surface. This surface is considered critical in terms of strength. The goal of this paper is to select a suitable crane hook for a single girder bridge crane with a load capacity of 500 kg and a strength analysis of the selected crane hook. Strength analysis is performed by two methods, first is based on analytical calculation and second is based on finite element method (FEM) performed in Ansys software. The comparison of the obtained total stresses from both methods is the part of the analysis. From the results of the FEM analysis and analytical calculation it can be stated that the selected crane hook RSN 05 P - DIN 15401 with a load capacity of 500 kg is suitable for the above-mentioned bridge crane. It can also be concluded that the total stress determined by the analytical calculation is lower by 9.8 % compared to the stress obtained from the Ansys software.